Studi Analisis Spasial Infiltrasi Di Das Kali Bodo Kabupaten Malang - Indarwati, Deni; Suhardjono, Suhardjono; Harisuseno, Donny (Fakultas Teknik, Universitas Brawijaya, 2014)
Infiltration process is one of the important processes in the hydrological cycle due to infiltration of determining the amount of rain water that seeped into the soil directly. This study aims to obtain mapping potential infiltration and recharge area. The approach used is KINEROS model, where the model was calibrated with field measurements using a turf-tec infiltrometer and tested with NSE statistical methods. Calibration results obtained after trial and error changes on three basic parameters in the model KINEROS, namely K (hydraulic conductivity of the soil), Gs (impulse capillary) and Por (porosity), also on the parameters of the Manning coefficient. After a change of 50% Manning coefficient and 75% value K, Gs and Por, test results obtained NSE = 0.460 which means that the model results are acceptable, and can be followed by a map showing the infiltration rate for and is used to determine the condition of the watershed Bodo.Key words: Infiltration, KINEROS, calibration.